Basic MR relaxation mechanisms and contrast agent design. Issue 3 (14th May 2015) - De León‐Rodríguez, Luis M.; Martins, André F.; Pinho, Marco C.; Rofsky, Neil M.; Sherry, A. Dean
<x xml:space="preserve">Abstract</x> The diagnostic capabilities of magnetic resonance imaging (MRI) have undergone continuous and substantial evolution by virtue of hardware and software innovations and the development and implementation of exogenous contrast media. Thirty years since the first MRI contrast agent was approved for clinical use, a reliance on MR contrast media persists, largely to improve image quality with higher contrast resolution and to provide additional functional characterization of normal and abnormal tissues. Further development of MR contrast media is an important component in the quest for continued augmentation of diagnostic capabilities. In this review we detail the many important considerations when pursuing the design and use of MR contrast media. We offer a perspective on the importance of chemical stability, particularly kinetic stability, and how this influences one's thinking about the safety of metal–ligand‐based contrast agents. We discuss the mechanisms involved in MR relaxation in the context of probe design strategies. A brief description of currently available contrast agents is accompanied by an in‐depth discussion that highlights promising MRI contrast agents in the development of future clinical and research applications. Our intention is to give a diverse audience an improved understanding of the factors involved in developing new types of safe and highly efficient MR contrast agents and, at the same time, provide an appreciation of the insights into physiology and disease that newer types of responsive agents can provide. J. Magn. Reson. Imaging 2015;42:545–565.